The p400 ATPase regulates nucleosome stability and chromatin ubiquitination during DNA repair - Xu, Ye; Sun, Yingli; Jiang, Xiaofeng; Ayrapetov, Marina K; Moskwa, Patryk; Yang, Shenghong; Weinstock, David M; Price, Brendan D (The Journal of cell biology, 2010)
The complexity of chromatin architecture presents a significant barrier to the ability of the DNA repair machinery to access and repair DNA double-strand breaks (DSBs). Consequently, remodeling of the chromatin landscape adjacent to DSBs is vital for efficient DNA repair. Here, we demonstrate that DNA damage destabilizes nucleosomes within chromatin regions that correspond to the γ-H2AX domains surrounding DSBs. This nucleosome destabilization is an active process requiring the ATPase activity of the p400 SWI/SNF ATPase and histone acetylation by the Tip60 acetyltransferase. p400 is recruited to DSBs by a mechanism that is independent of ATM but requires mdc1. Further, the destabilization of nucleosomes by p400 is required for the RNF8-dependent ubiquitination of chromatin, and for the subsequent recruitment of brca1 and 53BP1 to DSBs. These results identify p400 as a novel DNA damage response protein and demonstrate that p400-mediated alterations in nucleosome and chromatin structure promote both chromatin ubiquitination and the accumulation of brca1 and 53BP1 at sites of DNA damage.